2014
DOI: 10.5603/ait.a2014.0065
|View full text |Cite
|
Sign up to set email alerts
|

What’s new in medical management strategies for raised intra-abdominal pressure: evacuating intra-abdominal contents, improving abdominal wall compliance, pharmacotherapy, and continuous negative extra-abdominal pressure

Abstract: In the future, medical management may play an increasingly important role in the prevention and management of intra-abdominal hypertension (IAH). A review of different databases was used (PubMed, MEDLINE and EMBASE) with the search terms 'Intra-abdominal Pressure' (IAP), 'IAH' , ' Abdominal Compartment Syndrome' (ACS), 'medical management' and 'non-surgical management' . We also reviewed all papers with the search terms 'IAH' , 'IAP' and 'ACS' over the last three years, only extracting those papers which showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 56 publications
(42 reference statements)
0
26
0
7
Order By: Relevance
“…Less morbid therapies have been described to manage or prevent IAH without the need to proceed to a full decompressive laparotomy [36][37][38][39]. It is now possible that we may wish to have an open abdomen in the sickest septic patient not because we have to, but because we want to.…”
Section: The Futurementioning
confidence: 99%
“…Less morbid therapies have been described to manage or prevent IAH without the need to proceed to a full decompressive laparotomy [36][37][38][39]. It is now possible that we may wish to have an open abdomen in the sickest septic patient not because we have to, but because we want to.…”
Section: The Futurementioning
confidence: 99%
“…176 Cheatham, et al 177 demonstrated in a multicentre trial of 132 ventilated patients that IAP increased by 1.5 and 3.6 mm Hg when patients were placed in the semi-recumbent position at 15º and 30º HOB respectively. However, these differences were less obvious in patients with IAP>20 mm Hg.…”
Section: Medical Managementmentioning
confidence: 99%
“…При паралитическом илеусе как одной из причин роста внутрибрюшного давления возможно применение лекар-ственной стимуляции, это доказывается успешным исполь-зованием ингибиторов ацетилхолинэстеразы [11][12][13][14][15][16]. Усилению перистальтики способствует также применение слабительных препаратов, что, однако, не находит своего отражения в доказательных исследованиях по лечению вну-трибрюшной гипертензии по данным литературы [17,18].…”
unclassified